2020
DOI: 10.3389/fpsyg.2020.01719
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Grandparental Caregiving in Chinese Older Adults: Reduced Lonely Dissatisfaction as a Mediator

Abstract: The purpose of the present study is twofold: (1) to investigate the differences in terms of physical and mental health between those who provide grandparental care and those who do not and (2) to explore the mechanism that connects grandparental caregiving and health-related outcomes. Methods: Two studies (a cross-sectional and a short-term longitudinal follow-up) were conducted. The cross-sectional study (Study 1) examined 148 older adults who provided grandparental care and another 150 older adults who did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…First, this study reveals a new type of elderhood that just started to emerge in China. Previous literature has shown that, rooted in filial piety, the ideal image of elderhood in Chinese society places high value on grandparents taking care of grandchildren to engage in intergenerational reciprocity and obtain psychological and economic well-being (Chang et al, 2020; Cong & Silverstein, 2008; Hoang & Kirby, 2020; Ikels, 2004; Low & Goh, 2015; Whyte, 1997). In contrast, the “self-reliant elders” underlines an emerging trend of departing from this cultural normative practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, this study reveals a new type of elderhood that just started to emerge in China. Previous literature has shown that, rooted in filial piety, the ideal image of elderhood in Chinese society places high value on grandparents taking care of grandchildren to engage in intergenerational reciprocity and obtain psychological and economic well-being (Chang et al, 2020; Cong & Silverstein, 2008; Hoang & Kirby, 2020; Ikels, 2004; Low & Goh, 2015; Whyte, 1997). In contrast, the “self-reliant elders” underlines an emerging trend of departing from this cultural normative practice.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past four decades, attending to the needs of adult children’s families has become a dominant constituent of Chinese elders’ aging life as the result of the changing family structure and culture (Burnette et al, 2013; Chang et al, 2020; Hoang & Kirby, 2020; Ko & Hank, 2014; Shea et al, 2020; Yan, 2018; Yang & Du, 2021; C. Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants volunteered through advertisements and presentations in senior centres in the Region of Murcia (Spain). The Short Form 36 Health Survey (SF-36) survey’s SD from a previous study was used to establish the power and sample size 21. With an estimated error of 2.59 points, the total sample size for this study consisted of 40 participants, which provided a power of 95% and a significance level of α=0.05.…”
Section: Methodsmentioning
confidence: 99%
“…With greater longevity and lower fertility, grandparent caregiving is increasingly available in China and worldwide, and its influencing factors on grandparent caregivers' health have drawn considerable scholarly attention [1][2][3]. A basic typology to describe grandparent caregiving is suggested by Baker and Silverstein [4]: primary care for grandchildren due to family crisis or parental out-migration and supplementary care to assist working parents.…”
Section: Introductionmentioning
confidence: 99%